Fractal and Euclidean descriptors of platelet shape - Kraus, Max-Joseph; Neeb, Heiko; Strasser, Erwin F. (Platelets, 2014)
Platelet shape change is a dynamic membrane surface process that exhibits remarkable morphological heterogeneity. Once the outline of an irregular shape is identified and segmented from a digital image, several mathematical descriptors can be applied to numerical characterize the irregularity of the shapes surface. 13072 platelet outlines (PLO) were segmented automatically from 1928 microscopic images using a newly developed algorithm for the software product Matlab R2012b. The fractal dimension (FD), circularity, eccentricity, area and perimeter of each PLO were determined. 972 PLO were randomly assigned for computer-assisted manual measurement of platelet diameter as well as number, width and length of filopodia per platelet. FD can be used as a surrogate parameter for determining the roughness of the PLO and circularity can be used as a surrogate to estimate the number and length of filopodia. The relationship between FD and perimeter of the PLO reveals the existence of distinct groups of platelets with significant structural differences which may be caused by platelet activation. This new method allows for the standardized continuous numerical classification of platelet shape and its dynamic change, which is useful for the analysis of altered platelet activity (e.g. inflammatory diseases, contact activation, drug testing).
EVALuna2:15973